Hotel room supply and demand in world heritage city of Melaka - Ab Rahman, Syakir Amir; Mohit, Mohammad Abdul; Bachok, Syahriah (IIUM Press, 2011)
Tourism is an exclusive economic opportunity that leads to lifestyle changes. It potentially brings vitality and economic as well as cultural dynamism to a place. Hence, in order to attract domestic and international tourists, many countries embark on intensive efforts by providing and developing travel sites as well as facilities to facilitate the demands. In fact, although the provision of modern attraction places such as amusement parks, complex skyscrapers and others are the approaches and strategies to promote the tourism industry, the diversity of natural and heritage resources are also known as one of the tourism assets for a country.